Evaluation of pea (Pisum sativum) germplasm for inheritance of resistance to powdery mildew (Erysiphe pisi) - AMAR SINGH, D.K. BANYAL*, JAYA CHAUDHARY and (Indian Phytopathology, 2015)
The germplasm lines of pea (Pisum sativum L.) were screened under natural and artificial epiphytotic conditions under field and greenhouse, respectively. Out of 317 lines, 6 pea genotypes (DPP 362, JP-501-A/2, DPP-1542EP, PMR-21, KMNR-894 and JI-1766) showed highly resistant reaction against powdery mildew (Erysiphe pisi DC ex. Saint-Amans) while, 59 were moderately resistant. In order to study the genetics of resistance in pea, 6 lines (JI-1559, JI-2480, IPF-P-2-5, DPP-13, DPP-25G, DPP-1542 EP) showing resistance to different pathotypes of Erysiphe pisi were crossed in diallel mating design along with susceptible cultivar ‘Lincoln’. Segregation pattern of F2population of six crosses under field and in vitro conditions revealed a ratio of 1 resistant to 3 susceptible (1:3) thereby indicating the presence of single recessive gene in donor parents, indicating that resistance in genotypes JI-1559, JI-2480, IPF- P- 2-5, DPP-13, DPP-25G and DPP-1542 EP is governed by single recessive gene.